Ujaran Kebencian dan Berita Bohong Berdasarkan Perspektif Sosiologi Hukum Ditinjau dari Undang - Undang Informasi dan Transaksi Elektronik - Rohayanti Rohayanti (Syntax Corporation Indonesia, 2024)
The purpose of this study is to examine and analyse the regulation of hate speech from a sociological perspective with a focus on Law Number 1 of 2024 which is the second amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions. This research uses the normative juridical method. The results show that fake news that is deliberately spread to damage someone's reputation is regulated in Article 28 paragraph 1 of the ITE Law which prohibits the dissemination of electronic information that is untrue or misleading and has an impact on material losses for consumers in electronic transactions. On the other hand, hate speech is regulated in Article 28 paragraph 2 which prohibits the dissemination of electronic information that incites or influences others to cause hatred or hostility towards individuals or groups based on attributes such as race, nationality, religion or gender. This includes insults, defamation, provocation and slander, all of which aim to create hostility among the public.